A THEORETICAL FRAMEWORK FOR IMPROVING HAND HYGIENE COMPLIANCE: A SYSTEMATIC REVIEW : A theoretical framework for improving hand hygiene - Motamed-Jahromi , Mohadeseh; Kaveh, Mohammad Hossein (Malaysian Journal of Science, 2022)
Evidence before the COVID-19 outbreak indicated that healthcare workers’ hand hygiene compliance had been low. Although hand hygiene compliance has improved during the COVID-19 pandemic, it's necessary to plan a tailored and targeted hand hygiene promotion strategy to maintain changes. Therefore, the aim of this review was to assess experimental theory-based studies on hand hygiene improvement in order to identify the best theory and constructs with higher effectiveness. The study design is a systematic review. The search strategy was developed, and Medline (PubMed), ProQuest, Web of Knowledge, Scopus, Cochrane Trials, and Science Direct databases were searched up to May 26, 2020, without time limitation. Review Manager 5.1 software was used to determine the risk of bias. Irrelevant articles, non-original articles, non-interventional studies, and those that lacked a theoretical framework were excluded. A total of eight articles were entered into the final analysis, including three randomized clinical trials and five quasi-experimental studies. In these studies, theories were reported at intrapersonal, interpersonal, and organizational levels. Moreover, some studies evaluated multifaceted interventions involving various levels of influence. Finally, we suggested an integrated multi-level approach to promote hand hygiene (IMAPH) with a comprehensive theoretical framework for designing interventions. Keywords: Healthcare workers, Hand hygiene, Theory-based intervention, Systematic review, Multi theory model